DIDACTIC FUNDAMENTALS OF TEACHING RHETORIC IN HIGHER EDUCATION EDUCATIONAL PEDAGOGICAL INSTITUTIONS - N.B. Holub (Academy of Cognitive and Natural Sciences, 2022)
In the article the basic approaches are defined and analyzed, the main didactic and specific principles which define modern sense of process of rhetoric training in the institute and provide its efficiency.